Latin American Private Pension Funds' Vulnerabilities - Jorge Guillén (Centro de Investigación y Docencia Económicas, A.C., 2011)
In the last years, we have been witnesses of significant large rates of return in most Latin American private pension fund institutions (ppf). This outstanding performance of funds can be explained by an economic boom in the region. However, these funds have lately been hampered in some countries, something that contrasts with the successful performance of private pension funds¿ returns. We measure management performance with the Data Envelopment Analysis (dea) technique, and test a sample of eight countries in Latin America to determine if there is any vulnerability in the private pension funds. The results are relevant for policy makers and regulators of pension funds.